(untitled) (Quinto Sol, 2021)
This paper analyzes the conceptions about national socialism and Peronism that different referents of the Peronist left presented in a round table cycle held in September 1972. An approach close to the theoretical-methodological proposal elaborated by Reinhart Koselleck for the study of political concepts is tested to allow to recover the contingent and changing dimension of the political ideas that predominated in the debates of the Peronist left at the beginning of the 1970s, and that makes it possible to inquire about the connections between Peronism and socialism that occurred during the period.